A nation destroyed: an existential approach to the distinctive harm of genocide. Issue 1 (2nd January 2017) - Lederman, Shmuel
ABSTRACT: In this article, I present a critique of existing approaches to the distinctive harm of genocide and offer an alternative approach. I draw on Hannah Arendt's unique conception of genocide, to suggest an 'existential' account of the harm of genocide. For Arendt, the distinctive loss in genocide was not a moral loss, strictly speaking, but rather an existential loss to humanity. By destroying a nation in whole or in part, genocide robs us of a variety of possible ways of experiencing and understanding the world. This approach, I argue, is original and valuable, and merits further consideration by anyone who is interested in the problem of genocide.